Talking dirty an analysis of Filipino toilet terms - Magtibay, Ma. Lia Karen S.; Calderon, Tina Marie T. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2010)
The research deals with euphemisms for toilet terms in Filipino. The primary objective of the study is to show the patterns of language use within the social variables sex, age and social class given the euphemisms for toilet terms in Filipino. Other objective are to identify the different Filipino euphemisms for toilet terms, and to describe linguistically the Filipino euphemisms used for toilet terms. The study deals with toilet terms for three bodily functions, namely defecation, urination, and menstruation. One concern of the sociology language is describing the generally accepted social organization of language usage within speech communities (Giglioli 46). In order to do this, the researcher conducted a survey among two hundred and forty-two (242) UP students. They were asked to rate toilet terms as preferred formal (euphemistic), preferred informal (euphemistic), dispreferred (dysphemistic). A frequency count was done to find out the patterns, if any, of the use of euphemisms within the three social factors mentioned above. The expressions classified as preferred informal were described using Joseph Williams' five semantic processes by which euphemisms are created. The research also discusses how euphemisms are used as politeness strategies when talking about taboo topics. Results show that the female and male respondents show considerable similarities in classifying the expressions for toilet terms. Also, among the four socioeconomic classes employed in the study, the upper and the middle classes display the least disparity in their classifications of toilet terms. Results also show that respondents are likely to classify children's language and borrowed terms as euphemisms. Finally, the respondents cited the desire to avoid offending other and habit as the primary reason for using euphemisms.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.